2001
DOI: 10.1023/a:1011167113067
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of IAP (inhibitor of apoptosis) proteins as predictors of response to chemotherapy in advanced non-small-cell lung cancer patients

Abstract: Our results indicate that: 1) there are differences in the level of expression and in the subcellular distribution of c-IAP1, c-IAP2, and XIAP in tumors derived from NSCLC patients. 2) The expression of c-IAP1, c-IAP2 and XIAP does not predict the response to chemotherapy in patients with advanced NSCLC. 3) The relation between expression of IAPs and chemosensitivity in cancer patients may be more complex than anticipated by in vitro data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
78
1
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(89 citation statements)
references
References 36 publications
9
78
1
1
Order By: Relevance
“…Comparable results to RCC were reported for the prognostic significance of XIAP in acute myeloid leukemia (30). Conflicting results have been reported for small cell lung carcinoma (15,31).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Comparable results to RCC were reported for the prognostic significance of XIAP in acute myeloid leukemia (30). Conflicting results have been reported for small cell lung carcinoma (15,31).…”
Section: Discussionmentioning
confidence: 98%
“…These findings implied that overexpression of XIAP in tumor cells may render the cells resistant to apoptotic stimuli and may survive following therapy. XIAP is expressed in normal tissues, however, overexpression of XIAP has been demonstrated in several cancers including lung cancer and prostate cancer (15,16). In addition, downregulation of XIAP sensitizes the resistant cancer cells to death receptor-or cytotoxic drug-induced apoptosis (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…It is also signi®cant to note that the so-called extrinsic, caspase-8 regulated, and intrinsic, caspase-9 regulated, cell death pathways appear to act synergistically to promote cell death (Engels et al, 2000;Ferreira et al, 2000;Lacour et al, 2001), as well as promote apoptosis in a more pathwaydependent manner. For example, caspase-9/Apaf-1/ cytochrome c activation following caspase-8 activation through mediator-molecules such as BID (Gross et al, 1999b) or BAR (Zhang et al, 2000), or alternatively, the activation of caspase-8 following caspase-9 and caspase-3 activation to augment and speed cell death (Tang et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Even so, p53 can modulate and enhance the STS-induced apoptotic response to some extent. Evidence exists for p53-dependent activation of the caspase-9 apoptosome (Soengas et al, 1999), as well as an essential role for capase-8 in transcriptionindependent apoptosis triggered by p53 (Ferreira et al, 2000). Furthermore, it has recently been demonstrated that while primary, untreated neuroblastoma tumors rarely harbor p53 mutations, chemotherapeutic drug treatment can induce p53 gene mutations in neuroblastoma tumors (Tweddle et al, 2001).…”
Section: Status and Expression Of The P53 Tumor Suppressor Gene In Thmentioning
confidence: 99%
“…For example, both IAPs were shown to be upregulated in colorectal carcinoma (Krajewska et al, 2005), a type of cancer that often carries ras oncogene (Bos et al, 1987). Furthermore, XIAP and cIAP2 are frequently upregulated in lung carcinoma (Ferreira et al, 2001;Hofmann et al, 2002), another malignancy that often carries oncogenic ras (Rodenhuis et al, 1988). In addition, expression of both IAPs tends to be elevated in prostate carcinoma (Krajewska et al, 2003), a disease that is often associated with increased levels of ErbB2 (Signoretti et al, 2000;Shi et al, 2001), an established inhibitor of anoikis (Reginato et al, 2003) and a known activator of Ras (Satoh et al, 1990).…”
Section: Discussionmentioning
confidence: 99%